Teacher Efficacy and Teacher Social Perception in Creative Teaching for Elementary School Teachers - Yaumil Fadhilah; Rose Mini Agoes Salim; Shahnaz Safitri (Universitas Pendidikan Ganesha, 2022)
Creativity is a competency that teachers need to have, especially in the learning process, to support the formation of creative thinking processes in children. Creative teaching needs to be applied especially in the learning of elementary school children because they are in a critical period in forming creative thinking processes. Teachers play a role in fostering and increasing creativity in children in elementary school. This study analyzes the correlation between teacher efficacy and teacher perceptions of creativity on creative teaching behavior during school learning. This study uses a quantitative approach. A sampling of data on 43 elementary school teachers from several cities in Indonesia was conducted using a simple random technique. The measuring tools used in this research are the Creativity Fostering Teacher Index (CFTI) and the Teaching for Creativity Scale (TFCS). The data obtained were tested quantitatively using simple linear regression analysis. The results showed that self-efficacy and teacher perceptions influence creativity and creative teaching behavior. Increased teacher efficacy has been proven to help teachers to form self-confidence in creative teaching. On the other hand, the teacher's perception of creativity will also affect teacher efficacy in applying creativity to the teaching and learning process.